Design and Implementation of an Agile-Based Electronic Prescription System for Neurological Medications - Sihombing, Denny Jean Cross (Jurnal Ekonomi, 2024)
This study addresses the complexity of managing neurological medication prescriptions by implementing an Agile-based electronic prescription system. The main issues faced in neurological medical practice are complex drug dosages, drug interactions, and effective patient monitoring. To tackle these problems, this research employs qualitative and quantitative methods, including user needs analysis, application development, and user acceptance evaluation. The study's findings indicate that implementing the Agile-based electronic prescription system enhances neuro-logical medical practice efficiency, safety, and service quality. This system provides flexibility and certainty in patient care by its ability to adapt to changes in patient conditions and treatment protocols. The primary contribution of this research is the development of an Agile-based electronic prescription system capable of addressing the complexity of managing neurological medication prescriptions. This study offers a new perspective on paradigm shifts in prescription management through technology-driven approaches, thereby contributing to advancing more targeted and improved healthcare services in the future.